2010
DOI: 10.1007/s12206-009-1205-7
|View full text |Cite
|
Sign up to set email alerts
|

Numerical analysis for the structural strength comparison of St. Jude Medical and Edwards MIRA bileaflet mechanical heart valve prostheses

Abstract: This paper presents a numerical analysis for the structural strength comparison of the St. Jude Medical bileaflet mechanical heart valve prosthesis with flat leaflet and the Edwards MIRA bileaflet mechanical heart valve prosthesis with curved leaflet. Computer aided engineering systems are used in the analysis. The blood fluid pressure is applied to both flat and curved leaflets of the bileaflet mechanical heart valve prostheses for the rigid body dynamic analysis to confirm the almost same dynamic characteris… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…Figure 1 shows a three-dimensional simplified geometry of the St. Jude bileaflet mechanical heart valve investigated in this research, which was chosen to be similar to previous studies [14,15]. The model geometry mainly consists of four parts: valve leaflets, aortic sinus, inlet, and outlet sections [16]. In the previous experimental study, the phenomenon of leaflet fluttering was only observed when the leaflets were in the fully open position, so the leaflets were assumed to be fixed in the fully open position to simplify the calculation.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 1 shows a three-dimensional simplified geometry of the St. Jude bileaflet mechanical heart valve investigated in this research, which was chosen to be similar to previous studies [14,15]. The model geometry mainly consists of four parts: valve leaflets, aortic sinus, inlet, and outlet sections [16]. In the previous experimental study, the phenomenon of leaflet fluttering was only observed when the leaflets were in the fully open position, so the leaflets were assumed to be fixed in the fully open position to simplify the calculation.…”
Section: Methodsmentioning
confidence: 99%